Evaluation of antinociceptive and anti-inflammatory effects of mitragyna speciosa korth - Shaik Mohamed Mossadeq, Wan Mastura (2012)
The leaves of Mitragyna speciosa Korth. are used for pain relief, as an antidiarrhoeal agent and as an energy booster. However, the underlying mechanism(s) of the antinociceptive and anti-inflammatory effects of this plant is unknown. Therefore, the role of Mitragyna speciosa crude methanol extract (MSME) in pain and inflammation using in vivo and in vitro models of nociception and inflammation was investigated in rodents. Antinociceptive effects were assessed using the writhing, hot plate and 2.5 % formalin tests while the mechanism of action (MOA) was studied using the 1% formalin test. The anti-inflammatory activity was evaluated using the carrageenan-induced paw oedema and the cotton pellet-induced granuloma tests while the MOA was studied by measuring the mechanical activity of isolated guinea pig ileum strips pretreated with MSME in an organ bath. The intraplantar tissues of the treated animals in the 2.5% formalin and edema tests were excised for histological observation at the end of the experiment. Results from the antinociceptive study showed that intraperitoneal administration of the extract at doses of 100 and 200 mg/kg produced significant (p<0.05) inhibition of mice writhing response by 39.64% and and 52.34%, respectively. Results from the hot plate test also showed that the extract at the dose of 200 mg/kg produced significant (p<0.05) increase in the latency time compared to control groups. However, in the 2.5% formalin test, the nociceptive activity was inhibited only at the highest dose of the extract (200 mg/kg) with an inhibition of 24% (Phase 1) and 96.4% (Phase 2), respectively. This effect was also reproducible in the 1% formalin test. In contrast, local pretreatment of the paw with naloxone, tetraethylammonium, glibenclamide, the NG-L-nitro-arginine methyl ester, methylene blue, apamin and charybdotoxin at designated doses significantly (p<0.05) reversed MSME-induced antinociception (200 mg/kg) in either one or both phases of the test. Results from the anti-inflammatory study indicated that mice which received 200 mg/kg MSME showed significant (p<0.05) reduction in the development of paw edema by 60% and 63%, four to five hours after carrageenan administration, respectively. The histological observations of rat paw tissues in the formalin and edema tests further substantiated the anti-inflammatory activity of the extract at the dose of 200 mg/kg. Furthermore, the formation of granuloma in rats which received MSME at the dose of 200 mg/kg was significantly (p<0.05) reduced (44.9%), compared to control groups. On the other hand, the extract exerted a spasmogenic effect at low concentrations (0.1-0.5mg/ml) followed by a relaxation of ileal activities at higher concentrations (1-5mg/ml). In addition, pretreatment of the ileum with extract (0.5-5mg/ml) produced significant (p<0.05) concentration-dependant inhibition of spasmogenicity when exposed to single submaximal contraction induced by serotonin and prostaglandin. In conclusion, results from the antinociceptive study suggested that MSME may activate the opioid receptor-NO-cyclic GMP-K+ channels pathway in addition to the opening of Ca2+-activated K+ channels at peripheral afferent neurons. Furthermore,the peripheral anti-inflammatory activity of MSME is mediated possibly through the serotonergic and cyclo-oxygenase receptor antagonism, thus, corroborating the use of plant in pain and inflammation.